If it's not what You are looking for type in the equation solver your own equation and let us solve it.
1=-9(2y-5)-2(2y-5)
We move all terms to the left:
1-(-9(2y-5)-2(2y-5))=0
We calculate terms in parentheses: -(-9(2y-5)-2(2y-5)), so:We get rid of parentheses
-9(2y-5)-2(2y-5)
We multiply parentheses
-18y-4y+45+10
We add all the numbers together, and all the variables
-22y+55
Back to the equation:
-(-22y+55)
22y-55+1=0
We add all the numbers together, and all the variables
22y-54=0
We move all terms containing y to the left, all other terms to the right
22y=54
y=54/22
y=2+5/11
| -√6x²-√6x=0 | | 2(x-4)^2+36=4 | | (x+2)(7x−11)=0 | | -1.1-6x=8.5 | | 35y-3=102 | | 2(x+11)^1/2=x+3 | | x-14=57 | | 11=-51y | | 3(u+2)+4=5(u-1)+4 | | 11=-52y | | S=4t^2 | | 3.9x=10.53 | | S=4t2 | | 28x+1=88x | | 2^x-1=(1/8)^3x | | m/(-15)-24=(-10) | | 7(k-8)=3(2k-4) | | .40x=30 | | 8-n-15=41 | | .96x=24 | | 3k+4=3(k+3)-5 | | 3a+8=2a+14 | | m/9-13=-16 | | r^2-12r+22=0 | | 5y^2-4y=0 | | 5m+10-8=7m-10 | | 2/3(12−9)+10=x+(−6)+10 | | -7x+5=7x+6 | | 0=1/2x+3 | | m/9-13=-2 | | -45-(-4x-16)=-9(2x-5)-(4x-10) | | 0.5x+(4/3)x=x+5 |